Power storage device and method of manufacturing the power storage device

JP2025025425AActive Publication Date: 2025-02-21PRIME PLANET ENERGY & SOLUTIONS INC +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023130169
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21
Estimated Expiration
2043-08-09

Smart Images

  • Figure 2025025425000001_ABST
    Figure 2025025425000001_ABST
Patent Text Reader

Abstract

To provide: a power storage device in which formation of cracks in a resin member can be curbed when the power storage device is placed at room temperature (25°C); and the like.SOLUTION: A power storage device 1 includes a case member 30, terminal members 50, 60, and resin members 70, 80 subjected to insert molding to fix the terminal member 50, 60, respectively, to the case member 30. The resin members 70, 80 each are made of a resin material 75 including a thermoplastic main resin 76 having a first glass transition temperature Tg1 equal to or higher than 70°C, a thermoplastic elastomer 77, and a filler 78. The elastomer 77 has a second glass transition temperature Tg2 that is equal to or higher than -10°C and equal to or lower than 20°C and a third glass transition temperature Tg3 equal to or lower than -40°C.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electricity storage device in which a terminal member is fixed to a case member constituting a case via a resin member, and to a method for manufacturing the electricity storage device. [Background technology]

[0002] A known power storage device is a battery in which positive and negative terminal members are fixed via a resin member to a case member (specifically, a rectangular plate-shaped case lid member) constituting a rectangular box-shaped case. Specifically, the positive and negative terminal members are inserted into insertion holes provided in the case lid member and extend from the inside to the outside of the case, and the resin member hermetically joins the case lid member and the terminal members while insulating them from each other, thereby fixing the terminal members to the case lid member.

[0003] In manufacturing such a battery, a resin member may be insert-molded. That is, the resin member is insert-molded in a state in which the terminal member is inserted into the insertion hole of the case lid member, and the terminal member is fixed to the case lid member via the resin member. For example, Patent Document 1 (see Figs. 2, 6, 7, etc.) is an example of a conventional technique for insert-molding a resin member in this way. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2022-079172 Summary of the Invention [Problem to be solved by the invention]

[0005] In order to fix the terminal member to the case lid member with a resin member, the resin member needs to have a certain degree of hardness. For this reason, a resin having a glass transition temperature Tg1 that is sufficiently higher than room temperature (25°C), such as polyphenylene sulfide (PPS: glass transition temperature Tg1 = 90°C), may be used as the main resin constituting the resin member. In addition, in order to further improve the strength of the resin member or to bring the linear expansion coefficient of the resin material constituting the resin member closer to the linear expansion coefficient of the metal constituting the terminal member or case member, fillers such as glass fiber, carbon fiber, ceramic powder, etc. may be further added to the resin material. On the other hand, in order to increase the toughness of the resin member, an elastomer that is easily elastically deformed may be further added to the resin material. The added elastomer disperses the stress applied to the resin member, and prevents the resin member from cracking or the crack from propagating when the resin member is molded and cooled to room temperature or during actual use of the battery.

[0006] However, even when a resin part is molded using a resin material containing such a main resin, elastomer, and filler, it has been found that when the temperature of the resin part is returned to room temperature (25°C) after molding, stress caused by the difference in thermal expansion between the case part and terminal part, and the resin part, can cause cracks (fissures) along the boundary due to cohesive failure in areas of the resin part near the boundary with the terminal part.

[0007] The present invention has been made in consideration of the current situation, and provides an electricity storage device in which a resin member is molded using a resin material containing a main resin, an elastomer, and a filler, the main resin having a first glass transition temperature Tg1 that is sufficiently higher than room temperature, and which can suppress the occurrence of cracks in the resin member when the electricity storage device is placed at room temperature (25°C), and a method for manufacturing the electricity storage device. [Means for solving the problem]

[0008] (1) One aspect of the present invention for solving the above problem is an electricity storage device comprising a case member having an insertion hole, a terminal member inserted into the insertion hole of the case member, and an insert-molded resin member that hermetically joins the case member and the terminal member while insulating them from each other and fixing the terminal member to the case member, wherein the resin member is made of a resin material including a thermoplastic main resin having a first glass transition temperature Tg1 (Tg1≧70) of 70°C or higher, a thermoplastic elastomer, and a filler, and the elastomer has a second glass transition temperature Tg2 (-10≦Tg2≦20) of -10°C or higher and 20°C or lower, and a third glass transition temperature Tg3 (Tg3≦-40) of -40°C or lower.

[0009] In the above-mentioned electricity storage device, among the resin materials constituting the resin member, the main resin has a first glass transition temperature Tg1 of 70° C. or higher, while the elastomer has a second glass transition temperature Tg2 of −10° C. or higher and 20° C. or lower, and a third glass transition temperature Tg3 of −40° C. or lower. This makes it possible to suppress the occurrence of cracks in the resin member when the electricity storage device is placed at room temperature (25° C.).

[0010] The reason for this is believed to be as follows: Since the main resin contained in the resin material has a glass transition temperature Tg1 that is sufficiently higher than room temperature, the main resin is in a glassy state at room temperature and is hard and has high strength but low toughness. Here, consider the case where the elastomer contained in the resin material has only one glass transition temperature Tg2, or has two glass transition temperatures Tg2 and Tg3, and both of these glass transition temperatures Tg2 and Tg3 are higher than room temperature or slightly lower than room temperature (specifically, -10 to 25°C) (i.e., -10°C or higher). In this case, when the temperature of the resin member is room temperature, the elastomer is in a glass state, or the room temperature is close to the glass transition temperatures Tg2 and Tg3, so the elastomer is in a hard state. Therefore, the resin member (resin material) becomes hard and elastic, and if there is a thermal expansion difference between the case member and the terminal member and the resin member, a large stress is applied to the resin member, and the resin member is likely to crack.

[0011] On the other hand, consider a case where the glass transition temperature Tg2 of only one of the elastomers or both of the glass transition temperatures Tg2 and Tg3 are sufficiently lower than room temperature (specifically, −40° C. or lower). In this case, the elastomer is in a sufficiently soft rubber-like elastic state when the temperature of the resin member is at room temperature. Therefore, if there is a difference in thermal expansion between the case member and the terminal member and the resin member, the elastomer is too soft and easily deforms, making it difficult to disperse stress sufficiently, and a large stress is applied to the main resin of the resin member, which makes the resin member prone to cracking.

[0012] In contrast, in the present invention, as described above, the elastomer contained in the resin material has a second glass transition temperature Tg2 that is slightly lower than room temperature (-10 to 20°C) and a third glass transition temperature Tg3 that is sufficiently lower than room temperature (-40°C or lower). Therefore, when the temperature of the resin member is at room temperature, a part of the elastomer is in a hard state because the second glass transition temperature Tg2 is close to room temperature, but the remaining part of the elastomer maintains sufficient softness because the third glass transition temperature Tg3 is sufficiently lower than room temperature, and it is considered that the elastomer as a whole has a moderate hardness (moderate softness). As a result, even if there is a thermal expansion difference between the case member and the terminal member and the resin member, the elastomer with a moderate hardness deforms and distributes the stress, so that the stress applied to the main resin of the resin member is reduced, and it is possible to suppress the occurrence of cracks in the resin member.

[0013] In addition, when the glass transition temperature Tg2 of only one of the elastomers or both of the glass transition temperatures Tg2 and Tg3 are within a temperature range (above -40°C and below -10°C) between the two temperature ranges (above -10°C and below -40°C) described above, the elastomer has an appropriate hardness even when the temperature of the resin member is at room temperature. Therefore, since the elastomer deforms and distributes the stress, it is considered that the stress applied to the main resin of the resin member is reduced and the resin member is less likely to crack. However, in these cases, if the holding temperature of the electricity storage device is only slightly lowered from room temperature (for example, by about 10 to 20°C), the hardness of the entire elastomer increases, and the effect of reducing stress by the elastomer tends to be easily counteracted.

[0014] In contrast, in the present invention, as described above, the elastomer has two glass transition temperatures that are separate from each other, the second glass transition temperature Tg2 that is slightly lower than room temperature (-10 to 20°C) and the third glass transition temperature Tg3 that is sufficiently lower than room temperature (-40°C or lower). Therefore, even if the temperature at which the electricity storage device is held drops slightly from room temperature, the elastomer maintains an appropriate level of softness, so that the stress reducing effect of the elastomer is maintained and cracks in the resin member can be suppressed.

[0015] Examples of the "electricity storage device" include secondary batteries such as lithium ion secondary batteries, sodium ion secondary batteries, and calcium ion secondary batteries, and capacitors such as lithium ion capacitors. The term "main resin" refers to the resin material that has the largest weight ratio among the resin materials that make up the resin material. Examples of the "thermoplastic main resin having a first glass transition temperature Tg1 of 70°C or higher" include thermoplastic resins such as polyphenylene sulfide (PPS), polyether ether ketone (PEEK), polytetrafluoroethylene (PTFE), and perfluoroalkoxyalkane (PFA) that have a first glass transition temperature Tg1 of 70°C or higher.

[0016] Examples of "thermoplastic elastomers" include thermoplastic polyurethane elastomers (TPU) obtained from diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI) and high molecular weight diols. Examples of high molecular weight diols include polyester diols (PES), polyether diols (PET), polycaprolactone diols (PCL), and polycarbonate diols (PCD). The elastomer may have two glass transition temperatures Tg2 and Tg3, or may be a mixture of an elastomer having only the second glass transition temperature Tg2 and an elastomer having only the third glass transition temperature Tg3.

[0017] Examples of the "filler" include glass fillers made of alkali glass, E glass, etc., alumina fillers made of alumina, potassium titanate fillers made of potassium titanate, etc. Examples of the shape of the "filler" include spherical, plate-like, fibrous, and needle-like shapes. The resin material may contain materials other than the above-mentioned main resin, elastomer, and filler.

[0018] The first glass transition temperature Tg1 is preferably 150° C. or lower (70≦Tg1≦150). The third glass transition temperature Tg3 is preferably −140° C. or higher (−140≦Tg3≦−40).

[0019] In order to more appropriately prevent cracks from occurring in the resin member, it is preferable to set the linear expansion coefficient α3 of the resin material close to the linear expansion coefficient α1 of the metal constituting the case member and the linear expansion coefficient α2 of the metal constituting the terminal member. Specifically, the linear expansion coefficient α3 of the resin material is set to α1±0.8×10 with respect to the linear expansion coefficient α1 of the metal constituting the case member and the linear expansion coefficient α2 of the metal constituting the terminal member. -5 (1 / K), and α2±0.8×10 -5 It is preferable to set it within the range of (1 / K).

[0020] (2) In the electricity storage device according to (1), the third glass transition temperature Tg3 may be equal to or lower than −60° C. (Tg3≦−60).

[0021] In order to ensure the weather resistance of an electricity storage device, the electricity storage device may be subjected to a thermal cycle test (upper limit temperature 65 to 90°C, lower limit temperature -40 to -20°C). It has been found that such a thermal cycle test may cause cracks to appear in the resin member near the boundary with the terminal member, and the cracks may progress to the point where the seal between the terminal member and the resin member is destroyed. When the power storage device is cooled below room temperature, the thermal expansion difference between the case member and the terminal member and the resin member becomes large, and the stress applied to the resin member becomes large, so the relationship with the lower limit temperature is particularly important. When the resin member reaches the lower limit temperature (-40 to -20°C) in a thermal cycle test, if the third glass transition temperature Tg3 of the elastomer is higher than or close to this lower limit temperature, the entire elastomer becomes in a hard glass state or in a hard state that has not yet reached glass transition. Therefore, the resin member (resin material) becomes hard and elastic, so that the thermal expansion difference between the case member and the terminal member and the resin member applies a large stress to the resin member, and it is considered that the resin member is likely to crack.

[0022] In contrast, in the above-mentioned electricity storage device, the third glass transition temperature Tg3 is set to Tg3≦−60(°C), which is sufficiently lower than the lower limit temperature (−40 to −20°C). Therefore, the elastomer maintains a suitable softness even at the above-mentioned lower limit temperature, so that the stress reducing effect of the elastomer can be maintained and the occurrence of cracks in the resin member can be suppressed. As a result, even if the electricity storage device is subjected to a thermal cycle test at a lower limit temperature of about −40 to −20°C, the sealing property between the terminal member and the resin member can be well maintained.

[0023] (3) In the energy storage device described in (1) or (2), it is preferable that the terminal seal portion of the terminal member to which the resin member is hermetically joined has a forest of terminal nanopillars with a height of 50 nm or more on its surface, the terminal nanopillars being formed by particles with a diameter of 100 nm or less derived from the metal constituting the terminal member being linked in a string-like manner, and the resin member is hermetically joined to the terminal seal portion by filling the spaces between the forest of terminal nanopillars with the resin material.

[0024] In the above-mentioned power storage device, the above-mentioned terminal nano-pillars stand in a forest on the surface of the terminal seal part of the terminal member, and a resin material is filled between these terminal nano-pillars to hermetically bond the resin member to the terminal seal part. This increases the bonding strength between the terminal seal part of the terminal member and the resin member, and makes it possible to maintain good sealing performance between the terminal member and the resin member.

[0025] In addition, examples of particles derived from the metal constituting the terminal member that constitutes the terminal nanopillar include particles made of the above metals, particles made of oxides of the above metals, and particles made of the above metals and oxides of the above metals.

[0026] (4) Still another aspect is a connector comprising a case member having an insertion hole, a terminal member inserted into the insertion hole of the case member, and an insert-molded resin member that hermetically bonds the case member and the terminal member while insulating them from each other, and fixes the terminal member to the case member, the resin member being made of a resin material including a thermoplastic main resin having a first glass transition temperature Tg1 (Tg1≧70) of 70° C. or higher, a thermoplastic elastomer, and a filler, the elastomer having a second glass transition temperature Tg2 (−10≦Tg and a third glass transition temperature Tg3 (Tg3≦-40) that is −40° C. or lower, the method including an insert molding step of insert molding the resin member with the terminal member inserted into the insertion hole of the case member, wherein the insert molding step molds the resin member using the resin material that includes the main resin having the first glass transition temperature Tg1, the elastomer having the second glass transition temperature Tg2 and the third glass transition temperature Tg3, and the filler.

[0027] In the manufacturing method of the above-mentioned electricity storage device, a resin material containing the above-mentioned main resin, elastomer and filler is used to mold the resin member in the insert molding process, so that an electricity storage device can be manufactured in which the generation of cracks in the resin member is suppressed when the electricity storage device is placed at room temperature (25°C).

[0028] (5) A method for manufacturing an electricity storage device as described in (4), wherein the terminal member, the terminal seal portion to which the resin member is airtightly joined, has a surface on which terminal nanopillars with a height of 50 nm or more are formed by particles with a diameter of 100 nm or less derived from the metal constituting the terminal member being linked in a string-like manner, and the resin member is airtightly joined to the terminal seal portion by filling the spaces between the forest of terminal nanopillars with the resin material, and further comprises, prior to the insert molding step, a terminal nanopillar formation step of irradiating the terminal seal portion of the terminal member with a pulsed laser beam while shifting the irradiation position, to form the forest of terminal nanopillars in the terminal seal portion, and the insert molding step may be a method for manufacturing an electricity storage device in which the resin member is molded while filling the spaces between the forest of terminal nanopillars of the terminal seal portion with the resin material.

[0029] In the above-mentioned method for manufacturing an electricity storage device, the above-mentioned terminal nano-pillars are formed on the surface of the terminal seal part by irradiating laser light as described above in the terminal nano-pillar formation step, so that the terminal nano-pillars can be easily formed in the terminal seal part. Then, in the insert molding step, the resin member is molded while filling the spaces between the terminal nano-pillars with resin material, so that the bonding strength between the terminal seal part of the terminal member and the resin member can be increased and the sealing performance between the terminal member and the resin member can be well maintained. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is a perspective view of a battery according to an embodiment. [Diagram 2] 1 is a partially cutaway cross-sectional view of a battery according to an embodiment of the present invention taken along the battery height direction and the battery width direction. [Diagram 3] 1A and 1B are enlarged cross-sectional views of the vicinity of the terminal member and the resin member of a battery according to an embodiment, where (a) is an enlarged cross-sectional view along the battery height direction and the battery width direction, and (b) is an enlarged cross-sectional view along the battery height direction and the battery thickness direction. [Figure 4] FIG. 2 is a partially enlarged cross-sectional view of the vicinity of the surface of a terminal seal portion (lid seal portion) in a battery according to an embodiment. [Diagram 5]FIG. 11 is an explanatory diagram showing a cross section of a resin material, relating to a method for measuring a linear expansion coefficient α3 of the resin material. [Figure 6] 2 is a flowchart of a method for manufacturing a battery according to an embodiment. [Figure 7] FIG. 2 is an explanatory diagram showing a terminal nanopillar forming step (lid nanopillar forming step) in the battery manufacturing method according to the embodiment. [Figure 8] 5A and 5B are explanatory views of an insert molding process in a manufacturing method for a battery according to an embodiment, where FIG. 5A shows a state in which a terminal member is inserted into an insertion hole in a case lid member, and FIG. 5B shows a state in which a resin member is molded. [Figure 9] 1 is a graph showing the relationship between the number of thermal cycles in a thermal cycle test and the length of a crack generated in a resin member for the lid assemblies according to an example and comparative examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 shows a perspective view of a battery (electricity storage device) 1 according to this embodiment, and FIG. 2 shows a partially cutaway cross-sectional view of the battery 1. FIG. 3 shows a partially enlarged cross-sectional view of the vicinity of the terminal members 50, 60 and the resin members 70, 80. FIG. 4 shows a partially enlarged cross-sectional view of the vicinity of the surfaces 52m, 62m of the terminal seal parts 52, 62. In the following description, the battery height direction AH, the battery width direction BH, and the battery thickness direction CH of the battery 1 are defined as the directions shown in FIG. 1 and FIG. 2. The battery 1 is a rectangular (rectangular) sealed lithium ion secondary battery that is mounted on vehicles such as hybrid cars, plug-in hybrid cars, and electric cars.

[0032] The battery 1 is composed of a case 10, an electrode assembly 40 housed in the case 10, a positive electrode terminal member 50 fixed to the case 10 via a resin member 70, and a negative electrode terminal member 60 fixed to the case 10 via a resin member 80. The electrode assembly 40 is covered in a bag-shaped insulating holder 7 made of an insulating film inside the case 10. An electrolyte 5 is also housed inside the case 10, a part of which is impregnated in the electrode assembly 40 and the remainder is pooled on the bottom wall of the case 10.

[0033] The case 10 is a rectangular parallelepiped box made of metal (aluminum in this embodiment), and is configured from a case body member 20 having a rectangular opening 20c and a bottomed square cylinder shape that houses the electrode body 40 therein, and a rectangular plate-shaped case lid member 30 that closes the opening 20c of the case body member 20. In this embodiment, the case lid member 30 corresponds to the above-mentioned "case member." The opening 20c of the case body member 20 and the peripheral portion 30f of the case lid member 30 are hermetically welded around the entire circumference. Case lid member 30 of case 10 is provided with a safety valve 11 that breaks and opens when the internal pressure of case 10 exceeds a valve opening pressure. Case lid member 30 is also provided with a liquid injection hole 30k that penetrates case lid member 30, and this liquid injection hole 30k is airtightly sealed with a disk-shaped sealing member 12 made of aluminum.

[0034] The electrode assembly 40 housed in the case 10 is a rectangular parallelepiped laminated type, in which a plurality of positive electrode plates 41 and a plurality of negative electrode plates 42 are alternately laminated in the battery thickness direction CH with separators 43 made of porous resin films interposed between them. The positive electrode plates 41, the negative electrode plates 42, and the separators 43 each have a rectangular shape extending in the battery height direction AH and the battery width direction BH. The positive electrode plate 41 is composed of a positive electrode current collector foil made of aluminum foil and a positive electrode active material layer containing positive electrode active material particles formed on both main surfaces of the positive electrode current collector foil. A part of the positive electrode current collector foil extends to one side BH1 in the battery width direction BH, and the positive electrode active material layer is not present on both sides, forming a positive electrode foil exposed portion. The positive electrode foil exposed portions of each positive electrode plate 41 overlap in the foil thickness direction to form a positive electrode current collector 40c. The positive electrode current collector 40c is electrically connected to a terminal member 50 described later.

[0035] The negative electrode plate 42 is composed of a negative electrode current collector foil made of copper foil and a negative electrode active material layer containing negative electrode active material particles formed on both main surfaces of the negative electrode current collector foil. A part of the negative electrode current collector foil extends to the other side BH2 in the battery width direction BH, and is an exposed negative electrode foil portion on both sides of the negative electrode current collector foil without the negative electrode active material layer. The negative electrode foil exposed portions of the negative electrode plates 42 overlap in the foil thickness direction to form a negative electrode current collector 40d. The negative electrode current collector 40d is electrically connected to a terminal member 60 described later.

[0036] The case lid member 30 has rectangular insertion holes 30h1 and 30h2 near the ends of one side BH1 and the other side BH2 in the battery width direction BH, respectively, penetrating the case lid member 30. A positive electrode terminal member 50 made of aluminum is inserted into one of the insertion holes 30h1, and the terminal member 50 is fixed to the case lid member 30 in a state insulated from the case lid member 30 via a resin member 70. A negative electrode terminal member 60 made of copper is inserted into the other insertion hole 30h2, and the terminal member 60 is fixed to the case lid member 30 in a state insulated from the case lid member 30 via a resin member 80.

[0037] The terminal members 50, 60 (see Fig. 3 in addition to Fig. 1 and Fig. 2) are made by pressing metal plates (aluminum plate for the positive electrode and copper plate for the negative electrode), and are composed of a rectangular plate-shaped terminal outer part 51, 61 located outside the case lid member 30 (upper side AH1 in the battery height direction AH) and extending in the battery width direction BH and the battery thickness direction CH, a terminal inner part 53, 63 located inside the case lid member 30 (lower side AH2 in the battery height direction AH) and extending in the battery height direction AH, and a terminal seal part 52, 62 connected to the terminal outer part 51, 61 and the terminal inner part 53, 63 via the insertion hole 30h1. The terminal seal part 52, 62 is bent at an end of one side CH1 in the battery thickness direction CH of the terminal outer part 51, 61 and extends to the lower side AH2, and penetrates a resin member 70, 80 described later in the battery height direction AH. The positive electrode terminal inner part 53 is welded to the positive electrode current collector 40c of the electrode body 40 at the tip of the lower side AH2, and is conductively connected to the positive electrode current collector 40c. The negative electrode terminal inner part 63 is welded to the negative electrode current collector 40d of the electrode body 40 at the tip of the lower side AH2, and is conductively connected to the negative electrode current collector 40d.

[0038] The surfaces 51m, 61m of the terminal outer parts 51, 61 have rectangular top surfaces 51ma, 61ma facing the upper side AH1, rectangular inner side surfaces 51mb, 61mb facing the lower side AH2, and end surfaces 51mc, 61mc connecting these, and among these, the inner side surfaces 51mb, 51mb and the end surfaces 51mc, 61mc are joined to the resin members 70, 80. However, in this embodiment, terminal nano-pillars, which will be described later, are not formed on these inner side surfaces 51mb, 61mb and end surfaces 51mc, 61mc.

[0039] On the other hand, the resin members 70, 80 are airtightly joined to the terminal seal parts 52, 62. Specifically, the surfaces 52m, 62m of the terminal seal parts 52, 62 have a first main surface 52ma, 62ma facing one side CH1 of the battery thickness direction CH, a second main surface 52mb, 62mb facing the other side CH2 of the battery thickness direction CH, and a pair of end surfaces 52mc, 62mc connecting them. As shown in FIG. 4, the surfaces 52m, 62m are forested with terminal nano-pillars 55, 65 formed by connecting particles 55p, 65p derived from the metals (aluminum for the positive electrode and copper for the negative electrode) constituting the terminal members 50, 60 in a string-like manner.

[0040] Specifically, the positive electrode terminal nanopillars 55 are composed of particles 55p made of aluminum and aluminum oxide, and the negative electrode terminal nanopillars 65 are composed of particles 65p made of copper and copper oxide. The particles 55p, 65p have a diameter Da of 100 nm or less (in this embodiment, Da is approximately 30 nm), and the terminal nanopillars 55, 65 have a height ha of 50 nm or more (in this embodiment, ha is approximately 200 nm). The resin members 70, 80 described later are hermetically bonded to the terminal seal parts 52, 62 by filling the spaces between the forest of terminal nanopillars 55, 65 with a resin material 75.

[0041] In addition, the resin members 70, 80 are airtightly joined to the lid seal parts 31, 32 surrounding the insertion holes 30h1, 30h2 of the case lid member 30 (see FIG. 3). Specifically, the lid seal parts 31, 32 have rectangular annular outer side surfaces 31m, 32m facing the outside (upper side AH1) and rectangular annular inner side surfaces 31n, 32n facing the inside (lower side AH2). On these surfaces, like the surface 52m of the positive electrode terminal seal part 52 (see FIG. 4), lid nanopillars 35 are formed by connecting particles 35p made of aluminum and aluminum oxide in a string-like manner. The diameter Da of the particles 35p is 100 nm or less (in this embodiment, Da is approximately 30 nm), and the height ha of the lid nanopillars 35 is 50 nm or more (in this embodiment, ha is approximately 200 nm). The resin members 70 and 80 described below are airtightly joined to the lid seal portions 31 and 32 by filling the spaces between the forest of lid nanopillars 35 with a resin material 75 .

[0042] Next, the resin members 70, 80 will be described (see Figs. 1 to 4). The resin members 70, 80 are joined to the case lid member 30 and the terminal members 50, 60 while insulating the case lid member 30 and the terminal members 50, 60, and fix the terminal members 50, 60 to the case lid member 30. In detail, the resin members 70, 80 are airtightly joined to the terminal seal parts 52, 62 by filling the spaces between the standing terminal nano pillars 55, 65 of the terminal seal parts 52, 62 of the terminal members 50, 60 with a resin material 75 described later. The resin members 70, 80 are airtightly joined to the lid seal parts 31, 32 by filling the spaces between the standing lid nano pillars 35 of the lid seal parts 31, 32 of the case lid member 30 with a resin material 75 described later.

[0043] The resin members 70, 80 consist of a resin outer portion 71, 81 located on the outside (upper side AH1) of the case lid member 30, and a resin inner portion 72, 82 located on the inside (lower side AH2) of the case lid member 30 and within the insertion holes 30h1, 30h2, and connected to the resin outer portion 71, 81. The resin members 70, 80 are made of a resin material 75 including a thermoplastic main resin 76 having a first glass transition temperature Tg1, a thermoplastic elastomer 77 having a second glass transition temperature Tg2 and a third glass transition temperature Tg3, and a filler 78. The first glass transition temperature Tg1 of the main resin 76 is 70°C or higher (Tg1≧70). The second glass transition temperature Tg2 of the elastomer 77 is -10°C or higher and 20°C or lower (-10≦Tg2≦20), and the third glass transition temperature Tg3 is -40°C or lower (Tg3≦-40), or even -60°C or lower (Tg3≦-60).

[0044] Specifically, in this embodiment, the main resin 76 is polyphenylene sulfide (PPS) and has a first glass transition temperature Tg1 of 90°C. Elastomer 77 is a thermoplastic polyurethane elastomer (TPU) made from 4,4'-diphenylmethane diisocyanate (MDI) and polyester diol (PES). This elastomer 77 has two glass transition temperatures, the second glass transition temperature Tg2 is Tg2 = 10°C, and the third glass transition temperature Tg3 is Tg3 = -70°C. The filler 78 is a fibrous (approximately 10 μm in diameter×300 μm in length) glass filler made of alkali glass. The weight ratio of the main resin 76, the elastomer 77, and the filler 78 is main resin:elastomer:filler=40:10:50.

[0045] Next, the linear expansion coefficient α3 of the resin material 75 will be described. The temperature range of each of the linear expansion coefficients α1, α21, α22, and α3 described below is −40 to 65° C. The linear expansion coefficient α1 of the aluminum constituting the case lid member 30 and the linear expansion coefficient α21 of the aluminum constituting the positive terminal member 50 are α1±0.8×10 -5 (1 / K), and α21±0.8×10 -5 The linear expansion coefficient α3 of the resin material 75 constituting the negative electrode resin member 80 is within the range of α1±0.8×10 -5 (1 / K), and α22±0.8×10 -5 It is within the range of (1 / K).

[0046] Specifically, in this embodiment, the linear expansion coefficient α1 of the aluminum constituting the case lid member 30 and the linear expansion coefficient α21 of the aluminum constituting the positive electrode terminal member 50 are expressed as follows: α1=α21=2.4×10 -5 (1 / K). The linear expansion coefficient α22 of copper constituting the negative electrode terminal member 60 is α22 = 1.7 × 10 -5 On the other hand, the linear expansion coefficient α3 of the resin material 75 constituting the resin members 70 and 80 is α3=2.3×10 -5(1 / K). Therefore, the relationship between these linear expansion coefficients α1, α21, α22, and α3 is α3 = α1 - 0.1 × 10 -5 (1 / K), α3=α21-0.1×10 -5 (1 / K), α3=α22+0.6×10 -5 (1 / K), and the above-mentioned α3 ​​= α1 ± 0.8 × 10 -5 (1 / K), α3=α21±0.8×10 -5 (1 / K), α22±0.8×10 -5 The (1 / K) relationship is satisfied.

[0047] Here, a method for measuring the linear expansion coefficient α3 of the resin material 75 will be described (see FIG. 5). In this embodiment, since the filler 78 contained in the resin material 75 is fibrous, when the filler 78 dispersed in the resin material 75 is oriented, the linear expansion coefficient α3 of the resin material 75 has a directional property. That is, when the filler 78 is oriented in the direction in which the surface spreads, the first direction linear expansion coefficient αM in the first direction MD (in FIG. 5, the direction spreading in the left-right direction and the direction perpendicular to the paper surface) along the longitudinal direction of the filler 78 and the second direction linear expansion coefficient αT in the second direction TD (in FIG. 5, the up-down direction) perpendicular to the first direction MD have different magnitudes. Therefore, the first direction linear expansion coefficient αM and the second direction linear expansion coefficient αT are obtained, respectively, and the average value is calculated to obtain the linear expansion coefficient α3 (α3=(αM+αT) / 2).

[0048] Specifically, the linear expansion coefficient αM in the first direction and the linear expansion coefficient αT in the second direction of the resin material 75 are obtained by digital image correlation (DIC). First, a rectangular parallelepiped test piece of the resin material 75 in which the filler 78 is oriented in the direction in which the surface spreads is prepared. The test piece is placed on a sample cooling and heating stage (for example, Japan High-Tech Co., Ltd.'s Large Sample Cooling and Heating Stage 10083L for Microscopes) so that the cross section along the first direction MD and the second direction (see FIG. 5) can be seen. Then, for the test piece in a state of 25° C., an initial image of the cross section of the test piece is obtained. The image is obtained using, for example, Keyence Corporation's Digital Microscope VHX-8000.

[0049] Then, the test piece is cooled to -40°C and then heated to 65°C, and images of the cross section of the test piece are obtained at each temperature of -40°C, 0°C, 25°C, 50°C, and 65°C. The obtained images are then analyzed using a DIC system (for example, GOM's DIC system ARAMIS), and an approximation line y=ax+b showing the relationship between temperature x and strain y in the first direction MD is obtained, and the slope a of this line is defined as the first direction linear expansion coefficient αM for the first direction MD. Also, an approximation line y=cx+d showing the relationship between temperature x and strain y in the second direction TD is obtained, and the slope c of this line is defined as the second direction linear expansion coefficient αT for the second direction TD. Furthermore, the average value of these is calculated ((αM+αT) / 2), and this is defined as the linear expansion coefficient α3.

[0050] In the battery 1 of this embodiment, among the resin material 75 constituting the resin members 70, 80, the main resin 76 has a first glass transition temperature Tg1 of 70° C. or higher, while the elastomer 77 has a second glass transition temperature Tg2 of −10° C. or higher and 20° C. or lower, and a third glass transition temperature Tg3 of −40° C. or lower. This can prevent cracks from occurring in the resin members 70, 80 when the battery 1 is placed at room temperature (25° C.). The reason for this will be explained in the “Test Results” section below.

[0051] Furthermore, in this embodiment, the third glass transition temperature Tg3 is set to Tg3≦−60(° C.), which is sufficiently lower than the lower limit temperature (−40 to −20° C.) of the thermal cycle test. Therefore, the elastomer 77 maintains a suitable softness even at the lower limit temperature, so that the stress reduction effect of the elastomer 77 can be maintained and the occurrence of cracks in the resin members 70, 80 can be suppressed. As a result, even if the battery 1 is subjected to a thermal cycle test at a lower limit temperature of about −40 to −20° C., the sealing property between the terminal members 50, 60 and the resin members 70, 80 can be well maintained. The thermal cycle test will be described later.

[0052] In this embodiment, terminal nano-pillars 55, 65 stand in a forest on the surfaces 52m, 62m of the terminal seal portions 52, 62 of the terminal members 50, 60, and a resin material 75 is filled between these terminal nano-pillars 55, 65 to hermetically bond the resin members 70, 80 to the terminal seal portions 52, 62. This increases the bonding strength between the terminal seal portions 52, 62 of the terminal members 50, 60 and the resin members 70, 80, and makes it possible to maintain good sealing performance between the terminal members 50, 60 and the resin members 70, 80.

[0053] Next, a manufacturing method of the battery 1 will be described (see Figs. 6 to 8). First, an unroughened case lid member (case member) 30Z is prepared. The unroughened case lid member 30Z is obtained by punching an aluminum plate into a predetermined shape and forming the liquid injection hole 30k, the insertion holes 30h1, 30h2, and the safety valve 11 therein. In addition, unroughened terminal members 50Z, 60Z are prepared. The unroughened positive terminal member 50Z is obtained by punching an aluminum plate into a predetermined shape and bending it. In addition, the unroughened negative terminal member 60Z is obtained by punching a copper plate into a predetermined shape and bending it.

[0054] Then, in the "terminal nanopillar formation step S1" (see Fig. 6), the terminal seal portions 52, 62 of the terminal members 50Z, 60Z are irradiated with pulsed laser light LC while shifting the irradiation position (see Fig. 7), to form terminal nanopillars 55, 65 standing in a forest on the surfaces 52m, 62m of the terminal seal portions 52, 62. As described above (also see Fig. 4), the terminal nanopillars 55, 65 are formed by particles 55p, 65p being linked together in a string-like shape to form a pillar shape.

[0055] In this embodiment, the irradiation conditions of the positive electrode laser are set to a wavelength of 1064 nm, a peak output of 5 kW, a pulse width of 150 ns, a pitch pb of 75 μm, and a spot diameter Db of 80 μm. The irradiation conditions of the negative electrode laser are set to a wavelength of 1064 nm, a peak output of 20 kW, a pulse width of 50 ns, a pitch pb of 60 μm, and a spot diameter Db of 75 μm. In the terminal seal parts 52 and 62, in the circular parts irradiated with the laser light LC in a plan view, the metals (aluminum for the positive electrode and copper for the negative electrode) near the surfaces 52m and 62m melt and become steam. After that, when the temperature of the steam decreases, the metals become particles 55p and 65p (particles 55p of aluminum and aluminum oxide for the positive electrode and particles 65p of copper and copper oxide for the negative electrode) and are deposited on the surfaces 52m and 62m of the terminal seal parts 52 and 62. By irradiating the terminal seal portions 52, 62 with the laser beam LC while shifting the irradiation position, the particles 55p, 65p are deposited in a string-like manner and bonded to form columns, thereby forming terminal nano-pillars 55, 65 standing in a forest.

[0056] Separately, in a "lid nanopillar formation step S2" (see FIG. 6), a pulsed laser beam LC is irradiated onto the lid seal portions 31, 32 of the case lid member 30Z while shifting the irradiation position (see FIG. 7), to form forests of lid nanopillars 35 on the outer surfaces 31m, 32m and inner surfaces 31n, 32n of the lid seal portions 31, 32. As described above (also see FIG. 4), the lid nanopillars 35 are formed into columns by particles 35p made of aluminum and aluminum oxide linked together in a string-like pattern. In this embodiment, the laser irradiation conditions are the same as those used for forming the terminal nanopillars 55 in the positive electrode terminal seal portion 52 in the terminal nanopillar formation step S1.

[0057] Next, in the "insert molding process S3" (see FIG. 6), with the terminal members 50, 60 inserted into the insertion holes 30h1, 30h2 of the case lid member 30, respectively, resin members 70, 80 are insert molded using a resin material 75 containing a main resin 76 having the aforementioned first glass transition temperature Tg1, an elastomer 77 having a second glass transition temperature Tg2 and a third glass transition temperature Tg3, and a filler 78 (see FIG. 8).

[0058] Specifically, the insert molding process S3 is performed using a molding die (not shown) having an upper die and a lower die. First, the case lid member 30 is placed at a predetermined position in the lower die, and the terminal members 50 and 60 are inserted into the insertion holes 30h1 and 30h2 of the case lid member 30, respectively (see FIG. 8(a)). After that, the upper die is moved toward the lower die to close the molding die. Next, molten resin material 75 is injected into each of the two cavities of the molding die. At that time, the resin material 75 is also filled between the terminal nano pillars 55 and 65 standing in the terminal seal parts 52 and 62, and between the lid nano pillars 35 standing in the lid seal parts 31 and 32, and the resin members 70 and 80 that are airtightly bonded to the terminal seal parts 52 and 62 and the lid seal parts 31 and 32 are molded, respectively (see FIG. 8(b)). Thereafter, the lid assembly 15 in which the terminal members 50, 60 are fixed to the case lid member 30 via the resin members 70, 80 is removed from the molding die.

[0059] Next, in the "electrode body connecting process S4" (see FIG. 6), an electrode body 40 is prepared by stacking a positive electrode plate 41, a negative electrode plate 42, and a separator 43, and the terminal inner portion 53 of the terminal member 50 of the above-mentioned lid assembly 15 is welded to the positive electrode current collecting portion 40c of the electrode body 40. Also, the terminal inner portion 63 of the terminal member 60 of the lid assembly 15 is welded to the negative electrode current collecting portion 40d of the electrode body 40. Thereafter, the electrode body 40 is wrapped in a bag-shaped insulating holder 7. Next, in the "electrode assembly accommodating / case forming process S5", a case body member 20 is prepared, the electrode assembly 40 covered with the insulating holder 7 described above is inserted into the case body member 20, and the opening 20c of the case body member 20 is closed with the case lid member 30. Then, the opening 20c of the case body member 20 and the peripheral portion 30f of the case lid member 30 are laser-welded airtightly all around to form the case 10 accommodating the electrode assembly 40 therein.

[0060] Next, in a "pouring and sealing step S6", electrolyte 5 is poured into case 10 through pouring hole 30k, and electrolyte 5 is impregnated into electrode body 40. Thereafter, pouring hole 30k is covered from the outside with sealing member 12, and sealing member 12 is laser-welded to case 10 airtightly. Next, in the "initial charging and aging step S7", a charging device (not shown) is connected to the battery 1 to perform an initial charge on the battery 1. After that, the initially charged battery 1 is left to stand for a predetermined time to age the battery 1. In this way, the battery 1 is completed.

[0061] As described above, in the manufacturing method of battery 1, in the insert molding process S3, the resin members 70, 80 are molded using the resin material 75 containing the aforementioned main resin 76, elastomer 77 and filler 78, so that it is possible to manufacture a battery 1 in which the occurrence of cracks in the resin members 70, 80 is suppressed when the battery 1 is placed at room temperature (25°C). Furthermore, in the terminal nano-pillar formation step S1, the terminal nano-pillars 55, 65 are formed on the surfaces 52m, 62m of the terminal seal parts 52, 62 by irradiating the laser light LC as described above, so that the terminal nano-pillars 55, 65 can be easily formed in the terminal seal parts 52, 62. Then, in the insert molding step S3, the resin members 70, 80 are molded while filling the spaces between the terminal nano-pillars 55, 65 with the resin material 75, so that the bonding strength between the terminal seal parts 52, 62 of the terminal members 50, 60 and the resin members 70, 80 can be increased and the sealing properties between the terminal members 50, 60 and the resin members 70, 80 can be well maintained.

[0062] (Test Results) Next, the results of a test carried out to verify the effects of the present invention will be described (see FIG. 9). As an example, a lid assembly 15 (see FIG. 8(b)) according to the above-mentioned embodiment was prepared. That is, the terminal nano-pillar forming step S1, the lid nano-pillar forming step S2, and the insert molding step S3 were carried out to obtain a lid assembly 15 in which the terminal members 50, 60 were fixed to the case lid member 30 via the resin members 70, 80. The resin material 75 used in the insert molding contains a main resin 76 having a first glass transition temperature Tg1 (=90°C), an elastomer 77 having a second glass transition temperature Tg2 (=10°C) and a third glass transition temperature Tg3 (=-70°C), and a filler 78. In this example, the first glass transition temperature Tg1 (=90°C) satisfies Tg1≧70(°C), the second glass transition temperature Tg2 (=10°C) satisfies −10≦Tg2≦20(°C), and the third glass transition temperature Tg3 (=−70°C) satisfies Tg3≦−40(°C).

[0063] On the other hand, as Comparative Example 1, a resin material 75 including a main resin 76 having a first glass transition temperature Tg1 (=90°C), an elastomer 77 having a second glass transition temperature Tg2 (=-60°C) and a third glass transition temperature Tg3 (=-80°C), and a filler 78 was prepared, and the above-mentioned lid assembly 15 was formed using this in the same manner as in the Example except for the above. In this Comparative Example 1, the first glass transition temperature Tg1 (=90°C) satisfies Tg1≧70(°C), and the third glass transition temperature Tg3 (=-80°C) satisfies Tg3≦-40(°C), but the second glass transition temperature Tg2 (=-60°C) does not satisfy -10≦Tg2≦20(°C).

[0064] As Comparative Example 2, a resin material 75 including a main resin 76 having a first glass transition temperature Tg1 (=90°C), an elastomer 77 having only a second glass transition temperature Tg2 (=-10°C), and a filler 78 was prepared, and the above-mentioned lid assembly 15 was formed using this in the same manner as in the Example except for the above. In this Comparative Example 2, the first glass transition temperature Tg1 (=90°C) satisfies Tg1≧70(°C), and the second glass transition temperature Tg2 (=-10°C) satisfies -10≦Tg2≦20(°C), but since the third glass transition temperature Tg3 does not exist, Tg3≦-40(°C) is not satisfied.

[0065] The lid assemblies 15 of the examples and comparative examples were kept at room temperature (25°C) (the temperatures of the resin members 70 and 80 were set at room temperature), and the length of the crack occurring in the portion of the positive electrode resin member 70 near the boundary with the terminal member 50 and the length of the crack occurring in the portion of the negative electrode resin member 80 near the boundary with the terminal member 60 were measured. As a result, in the examples, no cracks occurred in either of the resin members 70 and 80. In FIG. 9, the length of the crack is shown as 0.0 mm when the number of thermal cycles n=0. Meanwhile, in Comparative Example 1, a 0.5 mm crack occurred in both of the resin members 70 and 80. Also, in Comparative Example 2, a 1.0 mm crack occurred in both of the resin members 70 and 80.

[0066] Next, these lid assemblies 15 were subjected to a thermal cycle test in a temperature range of a lower limit temperature of -40°C and an upper limit temperature of 65°C, taking into consideration the temperature conditions under which the battery 1 is used. Specifically, using a liquid bath tester, the lid assemblies were immersed in a liquid bath at -40°C for 3 minutes, and then immersed in a liquid bath at 65°C for 3 minutes, which constitutes one cooling / heating cycle, and this cycle was repeated n=4000 times. After n=1000, 2000, 3000, and 4000 cooling / heating cycles, the lengths of the cracks occurring in the resin members 70 and 80 were measured as described above. The results are shown in FIG. 9. In this test, since there was no difference in the size of the crack between the positive electrode resin member 70 and the negative electrode resin member 80, the resin members 70 and 80 are not distinguished in Fig. 9. In addition, since the seal length between the terminal members 50, 60 and the resin members 70, 80 is 2.5 mm, the maximum crack length in this test is 2.5 mm (when the crack length is 2.5 mm, the seal between the terminal members 50, 60 and the resin members 70, 80 is destroyed).

[0067] As is clear from the graph in Fig. 9, in the examples, no cracks were generated in the resin members 70, 80 even after the thermal cycle test. On the other hand, in Comparative Example 1, the cracks grew as the number of thermal cycles n increased, and the length of the cracks reached 2.5 mm at the number of thermal cycles n = 3000, destroying the seal between the terminal members 50, 60 and the resin members 70, 80. In Comparative Example 2, the cracks grew as the number of thermal cycles n increased, and the length of the cracks reached 2.5 mm at the number of thermal cycles n = 4000, destroying the seal between the terminal members 50, 60 and the resin members 70, 80.

[0068] The reason for this result is considered to be as follows: In other words, in each of the example and comparative examples 1 and 2, the main resin 76 contained in the resin material 75 has a first glass transition temperature Tg1 (=90° C.) sufficiently higher than room temperature, so that the main resin 76 is in a glassy state at room temperature and is hard and has high strength but low toughness. In Comparative Example 2, the elastomer 77 has only the second glass transition temperature Tg2, and this second glass transition temperature Tg2 (=-10°C) is in the range of -10°C or higher (higher than room temperature or slightly lower than room temperature). In such a case, when the temperature of the resin members 70, 80 is at room temperature, the elastomer 77 is in a hard state even if it is not in a glass state. Therefore, the resin members 70, 80 are hard and highly elastic, and a large stress is applied to the resin members 70, 80 due to the thermal expansion difference between the case lid member 30 and the terminal members 50, 60 and the resin members 70, 80, causing cracks in the resin members 70, 80. Furthermore, it is considered that the cracks grow by repeatedly changing the temperature of the lid assembly 15 in the thermal cycle test, and the seal between the terminal members 50, 60 and the resin members 70, 80 is destroyed.

[0069] In Comparative Example 1, the elastomer 77 has a second glass transition temperature Tg2 (=-60°C) and a third glass transition temperature Tg3 (=-80°C), both of which are sufficiently lower than room temperature (-40°C or lower). In such a case, the elastomer 77 is in a sufficiently soft rubber-like elastic state when the temperature of the resin members 70, 80 is at room temperature. Therefore, if there is a thermal expansion difference between the case lid member 30 and the terminal members 50, 60 and the resin members 70, 80, the elastomer 77 is too soft and easily deformed, and stress cannot be sufficiently dispersed, so that a large stress is applied to the main resin 76 of the resin members 70, 80, and a crack occurs in the resin members 70, 80. Furthermore, it is considered that the crack extends by repeatedly changing the temperature of the lid assembly 15 in the thermal cycle test, and the seal between the terminal members 50, 60 and the resin members 70, 80 is destroyed.

[0070] In contrast, in the embodiment, the elastomer 77 has a second glass transition temperature Tg2 (=10°C) that is slightly lower than room temperature (-10 to 20°C) and a third glass transition temperature Tg3 (=-70°C) that is sufficiently lower than room temperature (-40°C or lower). Therefore, when the temperature of the resin members 70, 80 is set to room temperature, a part of the elastomer 77 is in a hard state because the second glass transition temperature Tg2 (=10°C) is close to room temperature, but the remaining part of the elastomer 77 maintains a sufficient softness because the third glass transition temperature Tg3 (=-70°C) is sufficiently lower than room temperature, and it is considered that the elastomer 77 as a whole has a suitable hardness (suitable softness). As a result, even if a difference in thermal expansion occurs between the case cover member 30 and the terminal members 50, 60 and the resin members 70, 80, the elastomer 77, which has moderate hardness, deforms and distributes the stress, reducing the stress applied to the main resin 76 of the resin members 70, 80, and no cracks occur in the resin members 70, 80.

[0071] Furthermore, in the embodiment, the third glass transition temperature Tg3 (=-70°C) of the elastomer 77 is set to be sufficiently lower than the lower limit temperature (-40°C), that is, Tg3≦-60(°C). Therefore, the elastomer 77 maintains a suitable softness even at the lower limit temperature (-40°C), so that the stress reduction effect of the elastomer 77 is maintained and cracks can be prevented from occurring in the resin members 70, 80. It is believed that this allows the sealing properties between the terminal members 50, 60 and the resin members 70, 80 to be maintained well even when a thermal cycle test is performed.

[0072] Although the present invention has been described above with reference to an embodiment, it goes without saying that the present invention is not limited to the embodiment and can be modified as appropriate without departing from the spirit of the present invention. [Explanation of symbols]

[0073] 1. Battery (energy storage device) 10 Cases 30 Case cover member (case member) 30h1, 30h2 Through holes 40 Electrode body 50,60 Terminal material 52,62 Terminal seal part 52m, 62m (Terminal seal part) surface 55,65 Terminal Nano Pillar 55p,65p particles 70,80 Resin material 75 Resin material 76 Main Resin 77 Elastomer 78 Filler α Linear expansion coefficient LC Laser Light S1 Terminal nano pillar formation process S3 Insert molding process

Claims

1. A case member having an insertion hole; a terminal member inserted into the insertion hole of the case member; a resin member formed by insert molding, the resin member hermetically joining the case member and the terminal member while insulating them from each other and fixing the terminal member to the case member; The resin member is made of a resin material including a thermoplastic main resin having a first glass transition temperature Tg1 of 70° C. or higher (Tg1≧70), a thermoplastic elastomer, and a filler. An electricity storage device, The elastomer is It has a second glass transition temperature Tg2 of -10°C or more and 20°C or less (-10≦Tg2≦20) and a third glass transition temperature Tg3 of -40°C or less (Tg3≦-40). Energy storage device.

2. The power storage device according to claim 1 , The third glass transition temperature Tg3 is −60° C. or lower (Tg3≦−60). Energy storage device.

3. The electricity storage device according to claim 1 or 2, The terminal member includes a terminal seal portion to which the resin member is hermetically joined, On the surface of the terminal member, terminal nano-pillars having a height of 50 nm or more are formed by connecting particles having a diameter of 100 nm or less derived from the metal constituting the terminal member in a string-like manner to form pillars, The resin member is The resin material is filled between the adjacent terminal nano-pillars and is airtightly bonded to the terminal seal portion. Energy storage device.

4. A case member having an insertion hole; a terminal member inserted into the insertion hole of the case member; a resin member formed by insert molding, the resin member hermetically joining the case member and the terminal member while insulating them from each other and fixing the terminal member to the case member; the resin member is made of a resin material including a thermoplastic main resin having a first glass transition temperature Tg1 of 70° C. or higher (Tg1≧70), a thermoplastic elastomer, and a filler; The elastomer has a second glass transition temperature Tg2 of -10°C or more and 20°C or less (-10≦Tg2≦20) and a third glass transition temperature Tg3 of -40°C or less (Tg3≦-40). A method for manufacturing an electricity storage device, comprising: an insert molding step of insert-molding the resin member in a state in which the terminal member is inserted into the insertion hole of the case member, The insert molding process includes: The resin member is molded using the resin material including the main resin having the first glass transition temperature Tg1, the elastomer having the second glass transition temperature Tg2 and the third glass transition temperature Tg3, and the filler. A method for manufacturing an electricity storage device.

5. A method for producing the electricity storage device according to claim 4, comprising the steps of: a terminal seal portion of the terminal member to which the resin member is airtightly joined has a surface on which terminal nano-pillars having a height of 50 nm or more stand in a row, the pillars being formed by particles having a diameter of 100 nm or less derived from a metal constituting the terminal member and linked together in a string-like manner; the resin member is configured such that the resin material is filled between the standing terminal nano-pillars and is airtightly joined to the terminal seal portion, a terminal nano-pillar forming step of irradiating the terminal seal portion of the terminal member with a pulsed laser beam while shifting an irradiation position thereof, prior to the insert molding step, to form the terminal nano-pillars standing in a forest on the terminal seal portion, The insert molding process includes: The resin member is molded while filling the spaces between the terminal nano-pillars of the terminal seal portion. A method for manufacturing an electricity storage device.

Citation Information

Patent Citations

  • Thermoplastic resin composition and injection-molded article therefrom

    JP2000309668A

  • Aluminum / resin / copper composite article, its manufacturing method, and lid member for sealed battery

    JP2011124142A

  • Metal member and method for manufacturing metal member

    JP2022028587A

  • Resin composition for injection molding and injection molded body

    JP2023112592A

  • Battery and battery manufacturing method

    JP2022079172A